Utilization of Cow Rumen into Biogas Using a Fixed Dome Reactor as an Alternative Energy in Deli Serdang Regency - Sidabutar, Rivaldi; Aulia, Destanul; Ginting, Nurzainah; Irvan; Trisakti, Bambang; Tulus; Nauly, Meutia (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Biogas is renewable energy that can be used as substitute of LPG and generator fuel. The utilization of waste into biogas has been implemented in Tadukan Raga Village, Sinembah Tanjung Muda (STM) Hilir District, Deli Serdang Regency since 2018 by building a facility for processing biomass into biogas by utilize rumen waste and cow dung at pilot scale. This facility has been handed over by the Ministry of Environment and Forestry to the community to manage independently. However, there is a problem in the lack of understanding of the community in the management, development and maintenance of this facility. This problem resulted in the abandonment of the biogas plant so that production and operations not running and some equipment requiring repairs. The purpose of this program is to strengthen and empower observer groups and users of biogas production facilities in Tadukan Raga Village. Therefore it is necessary to carry out: an analysis of the sustainability of the biogas plant program and the use of biogas as an alternative to overcoming livestock manure pollution in the program of Desa Binaan USU 2022, repair of biogas reactor and piping and the use of biogas stoves modified from LPG stoves.